Kajian Living Qur’an Surat At-Taubah Dalam Tradisi Mitoni Di Bulus Pesantren Kebumen - Bistara, Raha; Indah Puspitasari, Ayuni (Al-Misykah: Jurnal Studi Al-qur'an dan Tafsir, 2024)
This article discusses the Islamization of culture through the Mitoni tradition with the reading of verses of the Qur'an in the form of QS. At-Taubah in Klapasawit Village, Buluspesantren, Kebumen. This study aims to find out the mitoni procession with thereading of QS. At-Taubah and know the reasons and objectives of the QS election. At-Taubah which was read during the Mitoni Tradition in Klapasawit Village. This study uses a qualitative research method with the type of field research and uses phenomenological approach. The primary data source in this study is the local community who practice the Mitoni Tradition. The secondary data sources are in the form of information from books, books and journals related to the object of research. Data collection through observation, interviews, and documentation. As a result of his research, the Mitoni Tradition procession began with a tasyakuran event in which QS read it. At-Taubah by seven people at the same time. After that, the procession continued at pregnant women who are being mitoni, making rujak, etc. The reason for the selection of QS. At-Taubah in the procession of the Mitoni Tradition in Klapasawit Village is because the meaning of the word at-Taubah itself means "forgiveness" or etymologically means "return". Thus, the purpose of the reading of QS. This at-Taubah is to remind, especially the pregnant woman to always return or repent to Allah so that her sins are forgiven and ask to always be given health and the safety of both mother and baby.